ASAS LEGITIMA PERSONA STANDI IN JUDICIO DALAM PERLAWANAN LELANG EKSEKUSI HAK TANGGUNGAN PIHAK KETIGA - Alyssa, Ima; Adlhiyati, Zakki (Sebelas Maret University, 2025)
The purpose of this article is to examine the implementation of the principle of Legitima Persona Standi in Judicio in opposition lawsuits against the execution of mortgage rights auction, as seen in Decision Number 4/Pdt.G/2024/PN Lmg. In this case, the opposing party acts as a third party replacing the position of the deceased debtor. Based on this, it is interesting to analyze whether the third party has legal standing as regulated under the principle of Legitima Persona Standi in Judicio. The principle of Legitima Persona Standi in Judicio plays a crucial role in determining the parties who have the right and capacity to file lawsuits in court, particularly in assessing the legal standing of third parties. The research method used in this study is normative or doctrinal legal research. The panel of judges assessed that the opposing party, who is the legitimate wife and legal heir of the debtor, has a legal interest in the auction object. The judges also considered the opposing party's legal relationship with the disputed object, including her involvement in the collateral agreement. In its ruling, the panel of judges stated that based on the principle of Legitima Persona Standi in Judicio, the opposing party as a third party has legal standing because she demonstrates good faith, a legal relationship, and fulfills the formal requirements as an heir under Articles 830 and 1100 of the Civil Code, as well as Article 163 of the HIR (Herzien Inlandsch Reglement). Moreover, the analysis concluded that the opposing party has a direct legal interest, possesses legal capacity (cakap hukum), and has suffered clear and tangible losses. Therefore, the opposing party meets the criteria to be considered a party with legal standing to file an objection to the auction.